To evaluate the expression j2 − 3k + j when j = 6 and k = 10, substitute the given values into the expression:
(6)2 − 3(10) + 6
= 36 - 30 + 6
= 6
Therefore, when j = 6 and k = 10, the expression j2 − 3k + j equals 6.
Evaluate the expression at specific values of their variables.(1 point)
Evaluate j2 − 3k + j, when j = 6 and k = 10
3 answers
u sure
Apologies for the mistake in my previous response. Let's re-evaluate the expression correctly.
The expression j^2 − 3k + j can be evaluated as follows:
j = 6
k = 10
(6)^2 − 3(10) + 6
= 36 - 30 + 6
= 42 - 30
= 12
Therefore, when j = 6 and k = 10, the expression j^2 − 3k + j equals 12.
The expression j^2 − 3k + j can be evaluated as follows:
j = 6
k = 10
(6)^2 − 3(10) + 6
= 36 - 30 + 6
= 42 - 30
= 12
Therefore, when j = 6 and k = 10, the expression j^2 − 3k + j equals 12.